2020
DOI: 10.1021/acs.energyfuels.0c02493
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption- and Diffusion-Controlled Wettability Change in Modified Salinity Water Flooding

Abstract: During the modified salinity water (MSW) flooding, the injected water must first reach and interact with the residual oil attached on the pore surfaces through a thin formation water film to mobilize the oil and improve the oil recovery. This can cause a delay in the rock response to the injection of MSW, as observed in many core flooding tests. The physicochemical processes that control this response time occur at two different scales: the alteration of wettability at the film scale and the consequent mobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“… 5 , 71 73 In most cases, the said smart water contains high and low dosages of SO 4 2– and divalent cations, respectively. 5 Smart water differs from LSW, which results from the dilution of formation brine [formation water (FW)] or SW. 27 These two terms have been erroneously used in the literature; 74 however, they mean two different brine systems. The effect of both brines has gained significant attention recently and continues to be an active area of research.…”
Section: Smart and Low Salinity Watermentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 71 73 In most cases, the said smart water contains high and low dosages of SO 4 2– and divalent cations, respectively. 5 Smart water differs from LSW, which results from the dilution of formation brine [formation water (FW)] or SW. 27 These two terms have been erroneously used in the literature; 74 however, they mean two different brine systems. The effect of both brines has gained significant attention recently and continues to be an active area of research.…”
Section: Smart and Low Salinity Watermentioning
confidence: 99%
“…Studies have shown that sulfate scales can alter the surface properties and wetting behavior of rock surfaces. ,, Although an extensive body of literature is available for bulk precipitation reactions, , only a limited number of published articles , focus on the effect of scales on rock surface chemistry which greatly influences its wetting behavior. Nikoo and Malayeri examined sulfate scale/brine/rock interfacial interactions and the rock wettability due to CaSO 4 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these experiments were performed to pinpoint the underlying mechanisms responsible for the recovery of oil. Different measurements such as contact angle, atomic force microscopy, core flooding, and spontaneous imbibition were executed at molecular to core scale to determine the effect of engineered water injection in carbonates (Taheriotaghsara et al, 2020). Strand et al (2006) and Zhang et al (2007) investigated the effect of increasing temperature and the concentration of potential determining ions in the injected water.…”
Section: Introductionmentioning
confidence: 99%
“…Attar et al 67,68 investigated the influence of geological heterogeneity on the oil recovery and water breakthrough time as a function of slug size of MSW injection during 17 The observed delay has been associated with the adsorptive transport of some key ions and the diffusion-controlled wettability alteration. 70 Upscaling such a delay to the reservoir scale without considering the presence of heterogeneity is equivalent to decades of waiting time. However, the analysis of oil production from a few field trials of MSW flooding shows that the timing of oil bank production coincides with MSW flooding injection.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of several MSW flooding tests in various types of homogeneous carbonate core plug samples (e.g., chalk, dolomite, limestone) revealed that tertiary oil breakthrough typically occurs after a 0.6 pore volume of MSW injection . The observed delay has been associated with the adsorptive transport of some key ions and the diffusion-controlled wettability alteration . Upscaling such a delay to the reservoir scale without considering the presence of heterogeneity is equivalent to decades of waiting time.…”
Section: Introductionmentioning
confidence: 99%